Experimental validation of online monitoring and optimization strategies applied to a biohydrogen production dark fermenter. (23rd November 2018) - Torres Zúñiga, Ixbalank; Villa-Leyva, Alberto; Vargas, Alejandro; Buitrón, Germán
Graphical abstract: Highlights: A coupled robust observer is validated in an experimental bioreactor. The observer is used for implementing a heuristic optimization strategy. Optimization strategy and coupled bioreactor are thoroughly explained. The application maximizes the hydrogen production rate in a dark fermenter. Abstract: This work presents the proposal and experimental validation of an online optimization strategy for maximizing the hydrogen production rate (HPR) in an anaerobic bioreactor through the dark fermentation of glucose. The proposal comprises a heuristic optimization strategy, a coupled nonlinear observer, and a PI controller to track the desired maximum HPR. The optimization is achieved by solving online a nonlinear programming problem which considers the relation between the HPR and the organic loading rate (OLR), such that the latter is manipulated to maximize the former. Since the OLR requires online knowledge of the unmeasured influent substrate concentration, the nonlinear observer is used to estimate it using measurements of the hydrogen flow rate at the output of the bioreactor. This observer comprises the coupled operation of a robust Luenberger observer and a super-twisting observer. The proposal was designed and tested experimentally in a continuous stirred tank laboratory bioreactor fed with glucose, and the results are very promising.